Pengaruh Karakteristik Aspal Modifikasi Getah Pinus Terhadap Peluruhan Campuran Aspal Porus: Effect of pine resin modified asphalt on the draindown of porous asphalt mixture - Ratna Yuniarti; Made Mahendra; I D M Alit Karyawan; Desi Widianty; Fera Fitri Salsabila (LPPM Universitas Mataram, 2023)
A porous asphalt mixture is a type of pavement that allows water to drain through, thereby reducing the amount of surface runoff and improving road safety. To drain water quickly, porous asphalt is dominated by coarse aggregate so that the voids in the mixture become larger. Draindown, which is the loss of asphalt binder from the mixture, can cause blockages and reduce the ability of the pavement to drain rainwater. The use of modified asphalt is expected to increase the bonding between the asphalt and aggregate to withstand loading but meet draindown requirements. The pine resin used as an asphalt modifier in this study was 2%, 3%, 4%, and 5%, whereas the percentage of gumrosin was 4% by weight of the modified asphalt. Modified asphalt testing includes the penetration, softening point, ductility, and weight loss. The mixing process of the aggregate with modified asphalt was carried out at 160 °C with asphalt contents of 4.5%, 5%, and 5.5% by weight of the asphalt mixture. The results showed that the penetration value, ductility, and weight loss of the modified asphalt increased, while the softening point decreased with the addition of pine resin. In general, the physical properties of the modified asphalt have a significant effect on the draindown value. Referring to the draindown specifications of the porous asphalt mixture (0.3 %), this requirement is fulfilled in all modified asphalt compositions and asphalt contents used in this study.